1997
DOI: 10.1074/jbc.272.33.20884
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Earthworm Hemolysin with Lipid Membranes Requires Sphingolipids

Abstract: Lytic activity in the coelomic fluid of earthworm (Eisenia fetida fetida) has been ascribed to eiseniapore, a hemolytic protein of 38 kDa. Since receptors for eiseniapore on target cell membranes are not known, we used lipid vesicles of various composition to determine whether specific lipids may serve as receptors. Lytic activity of eiseniapore was probed by the relief of fluorescence dequenching from the fluorophore 8-aminonaphthalene-1,3,6-trisulfonic acid originally incorporated into the vesicle lumen as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 54 publications
2
40
0
Order By: Relevance
“…Consistently, it has been reported that antibody binding to antigens on liposomes (34) and the interaction of hemolysin with the lipid membrane (35) are enhanced in the presence of cholesterol.…”
Section: Discussionsupporting
confidence: 59%
“…Consistently, it has been reported that antibody binding to antigens on liposomes (34) and the interaction of hemolysin with the lipid membrane (35) are enhanced in the presence of cholesterol.…”
Section: Discussionsupporting
confidence: 59%
“…Another research group has recently found that a cytolysin (named eiseniapore) purified from the earthworm E. foetida recognizes SM (24). Interestingly, eiseniapore binds to both SM and galactosylceramide (24), whereas lysenin shows no significant crossreaction with galactosylceramide (10), and the specific product of the lysenin cDNA binds specifically to SM, 2 suggesting that eiseniapore is a distinct molecule from lysenin. Eiseniapore may be a lysenin-like protein with a broader substrate specificity than lysenin, although confirmation of this possibility should await cDNA cloning of eiseniapore.…”
Section: Discussionmentioning
confidence: 99%
“…Linder and Bernheimer (32) observed nearly two decades ago that the cytolytic activity of several pore-forming toxins was decreased by the depletion of membrane cholesterol. Since that time, the presence of membrane cholesterol has been found to enhance pore formation for the sea anenome-derived pore-forming toxin sticholysin II (33), Staphylococcus aureus alpha hemolysin (34), aerolysin (35), the earthworm-derived hemolysin eiseniapore (36), the Escherichia coli hemolysin ClyA (SheA) (37), and the Vibrio cholerae hemolysin (38). One explanation for the common enhancement of pore-formation is that cholesterol may interact with these toxins in such a way as to promote insertion of their transmembrane domains and͞or by the promotion of certain membrane structures (inverted hexagonal phases) (39) that may facilitate the insertion of the transmembrane domains.…”
Section: Discussionmentioning
confidence: 99%